STUDY OF ONLINE CITIZEN SERVICES IN PUNJAB (Global Journal of Advanced Engineering Technologies and Sciences, 2014)
Government is spending huge amount of money on digitization of citizen services to provide these via e-delivery. Punjab government has done a commendable job to provide e-services to its people. In this paper, various online services provided to citizens of Punjab state of India has been studied and various measures are suggested to make it more effective. The biggest hindrance in success of e-services is ignorance and lack of awareness about the services between people. The full participation of both citizens and employees can make it truly a right tool for welfare of people.